A Study on Retail Investors Behaviour on Equity Shares – A Special Reference to Kanyakumari District (International Journal of Food and Nutritional Sciences, 2022)
An Economy of a country progresses when its savings are mobilized in the form of investments and the leakages of the consumption pattern changes in giving an injection to the Economy. As per the economic thought savings are leakages from the consumption pattern and all investments are injections in enhancing capital formation of an economy. There are avenues open to the retail investors where they can realize their savings in getting better returns. Capital market is the backbone of any country’s economy. It is an engine for economic growth, providing an efficient means of resource mobilisation and allocation. The Indian Capital Market comprises of two segments, namely, the Primary and the Secondary market. The fresh issue of securities takes place in primary market and trading among investors takes place in secondary market. Generally, the Indian corporates mainly raise funds through capital market. Two types of capital are essentially raised viz., Equity and Debt. The capital raised through equity is superior to that of debt capital for both the firm and the investor. Equity enhances the borrowing power of the firm from banks and financial institutions. This study focuses on Retail Investors Behaviour on Equity Shares in Kanyakumari District. For that, the researcher circulated 50 sample and analysed socio economicbackground of sample respondents, source of information getting by the respondents and compare the Socio-Economic Characteristics and Category of investors. The researcher used percentage and chi-squre test for this study.